Identificación morfológica y molecular de la cepa nativa de (metarhizium spp) 2023-2024 - Guamantaqui Cruz, Edison Gustavo (2024)
The objective of this research project was to comprehensively determine the morphological and molecular identification of a native strain of Metarhizium spp., that were stored in the laboratory of the agronomy department. For this purpose, multiplication techniques such as swabs, sticks and sowing loop were used. It was determined that the swabs proved to be the most effective for obtaining Metarhizium spp., since they showed greater sterility and were able to inhibit contamination in the Petri dishes for the most part. The boxes that were successfully purified showed the morphological structures of Metarhizium spp. Subsequently, to be sure, these samples were sent to the BIOHACK laboratory located in Quito for the relevant molecular identification analysis. The results obtained indicated that 100% of the samples contained a single species, which was identified as Metarhizium anisopliae. This research project will contribute significantly to the understanding and characterization of Metarhizium anisopliae, which has important implications for its effective application in the biological control of agricultural and forestry pests, thus promoting sustainable and environmentally friendly practices in crop and ecosystem management.